The deepest kill [large type] - Black, Lisa, 1963- (Black, Lisa, 1963- Locard Institute thriller, 2024)
"For software pioneer Martin Post, the third richest man in America, his private compound on the Florida coast is a sunny no-man's-land separating his family from the rest of the world. Now, expert forensic analysts Ellie Carr and Rachael Davies of the renowned Locard Institute have been summoned to its dark side. Martin's pregnant daughter, Ashley, had ventured on a day trip in her motorboat into the Gulf, only to wash up dead on a nearby shore. Although the local coroner determined her death was an accident, Ellie and Rachael soon confirm Martin's gravest fear: His daughter was murdered. Was it a kidnapping gone wrong? Or something even more brutal? Ashley and her husband, Greg, had been working with Martin on a revolutionary new defense initiative for the US military -- could espionage have played a part in her death? Martin believes Greg is behind the murder, and the spoiled charmer does set off Rachael's deception radar. Drawn into the Posts' increasingly dangerous family dynamic, Ellie and Rachael must work hard and fast to discover what secrets are buried at the heart of the crime -- because the churning waters of the Gulf are getting rougher. And soon, Ellie and Rachael themselves will be in danger of getting crushed in their depths."--